2019
DOI: 10.3233/kca-180047
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapy and Immunotherapy: Effect of Body Mass Index on Clinical Outcomes in Patients Diagnosed with Metastatic Renal Cell Carcinoma

Abstract: Background: Previous research has identified an association between high body mass index (BMI) and better overall survival (OS) in metastatic renal cell carcinoma (mRCC) patients treated with vascular endothelial growth factor-tyrosine kinase inhibitors (VEGF-TKIs). Objective: The current study sought to determine whether the effect of BMI on OS extends beyond VEGF-TKIs to mTOR inhibitors or immunotherapy (IO). Design, Setting and Participants: A retrospective study was conducted among patients diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…One of these studies, by Bergerot et al, found that elevated BMI was beneficial when RCC patients received targeted therapies such as VEGF or mTOR inhibitors, but found a detrimental trend when immune checkpoint inhibitors were used at the same institution. 18 A 2019 report by Sanchez et al examined retrospective outcomes from an observational cohort of RCC patients (n=203) treated at Memorial Sloan Kettering between 2011 and 2018 with immune checkpoint inhibitors (monotherapy or any combination of anti-PD-1/PD-L1/CTLA-4). 16 In this cohort, obesity was not associated with increased mortality after adjusting for IMDC risk score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these studies, by Bergerot et al, found that elevated BMI was beneficial when RCC patients received targeted therapies such as VEGF or mTOR inhibitors, but found a detrimental trend when immune checkpoint inhibitors were used at the same institution. 18 A 2019 report by Sanchez et al examined retrospective outcomes from an observational cohort of RCC patients (n=203) treated at Memorial Sloan Kettering between 2011 and 2018 with immune checkpoint inhibitors (monotherapy or any combination of anti-PD-1/PD-L1/CTLA-4). 16 In this cohort, obesity was not associated with increased mortality after adjusting for IMDC risk score.…”
Section: Discussionmentioning
confidence: 99%
“…We began by examining survival outcomes of RCC patients with and without obesity following anti-PD-1 treatment. Recent retrospective studies investigating Open access the effects of obesity on immunotherapy outcomes in RCC have provided intriguing but conflicting results: that increased adiposity (defined as BMI >25 kg/m 2 ) trended toward being detrimental, 18 that obesity (BMI >30 kg/m 2 ) had no impact on outcomes in multivariate analysis, 16 or that obesity improved PFS but not OS in patients who showed primary clinical benefit. 19 We examined this issue by evaluating outcome data for all RCC patients treated with standard of care anti-PD-1 who had ≥6 months of follow-up from treatment initiation at the UAB Hospital (n=54) and the UI Hospitals and Clinics (n=18).…”
Section: Obesity Is Associated With Poorer Pfs and Os In Metastatic Rmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the difference failed to reach statistical significance after adjusting for IMDC risk score. As a contradiction, an inverse trend was reported by Bergerot et al [71], where a small group of immunotherapy-treated metastatic RCC patients with low BMI had a median OS of 23.6 months compared to 19.9 months in overweight/obese patients. A study by Labadie et al [72] reported that BMI was not correlated with OS in ccRCC patients with primary resistance to immunotherapy, while the correlation was positive in immunotherapy-sensitive patients.…”
Section: Introductionmentioning
confidence: 89%
“…116 Bergerot et al have recently described a similar trend on a smaller case series. 117 In metastatic EGFR-mutated non-small cell lung cancer (NSCLC), however, no correlation has been found between patient nutritional status (defined by BMI, body weight and BSA) and response to gefitinib, 118 whereas a potential higher risk of grade 2 hepatic dysfunction has been observed in overweight subjects. 119 As for other targeted agents, BMI did not impact on molecular RR of nilotinib and dasatinib, while a delayed and low rate of molecular responses were observed for imatinib as frontline treatment in obese patients, probably due to the effect of the drug on signaling regulation of macrophages via platelet-derived growth factor (PDGF) receptors adipogenesis stimulation.…”
Section: Targeted Therapies and Immune Checkpoint Inhibitors In Overweight And Obese Patientsmentioning
confidence: 99%